THE EFFECT OF FOREIGN INVESTMENT AND BANKING CREDIT ON ECONOMIC GROWTH IN EAST NUSA TENGGARA PROVINCE - Sari Ka, Desna (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
This research aims to analyze the influence of foreign investment and banking credit on economic growth in East Nusa Tenggara Province in the 2021-2023 period. The research method used is quantitative with an explanatory approach, using secondary data in the form of Foreign Direct Investment (FDI) values, total banking credit, and Gross Regional Domestic Product (GRDP). Data analysis was carried out using panel data regression. The research results show that partially the foreign investment variable has a significant influence on economic growth in East Nusa Tenggara, while bank credit has no significant influence. However, foreign investment and banking credit simultaneously influence economic growth even though their contribution is still limited, with an Adjusted R-squared value of 0.030. This indicates that other factors outside research are still more dominant in influencing regional economic growth. These findings indicate the importance of government policy in attracting foreign investment as well as